2011
DOI: 10.5230/jgc.2011.11.4.200
|View full text |Cite
|
Sign up to set email alerts
|

Aging over 70 Years Is Not a Decisively Dismal Prognostic Factor in Gastric Cancer Surgery

Abstract: PurposeGastric cancer has a high incidence and mortality rate in Korea. Despite a growing older population and an increase in the number of older patients with gastric cancer, the older patients are not willing to undergo surgery due to their operative risks. Hence, to determine the clinical characteristics and outcomes of gastric cancer surgery for them, we investigate factors influencing the treatment decision.Materials and MethodsBetween January 1996 and December 2005, a total of 1,519 patients were classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Even the median length of hospital stay was similar in both age groups. As our study does, there has been increasing numbers of reports older patients should not be excluded in any types of surgical indications, not only on gynecologic operation, but also on other surgical parts [ 7 ]. Most of the authors say elderly patients can undergo surgery even in the ninth and tenth decade of their life and the perioperative morbidity and mortality have been decreased during the last decade thanks to the advances in anesthesia and surgical techniques and improvement in perioperative care [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even the median length of hospital stay was similar in both age groups. As our study does, there has been increasing numbers of reports older patients should not be excluded in any types of surgical indications, not only on gynecologic operation, but also on other surgical parts [ 7 ]. Most of the authors say elderly patients can undergo surgery even in the ninth and tenth decade of their life and the perioperative morbidity and mortality have been decreased during the last decade thanks to the advances in anesthesia and surgical techniques and improvement in perioperative care [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some reports demonstrated no significant difference in the mean hospital stay as our study did [ 11 ]. Although it is for the gynecologic oncological patients, Giannice et al found no correlation between severe comorbidities and median hospital stay [ 7 , 12 ].…”
Section: Discussionmentioning
confidence: 99%